How to Plan and Strategically Manage an Electric Vehicle (EV) Charging Station (Global Journal of Management and Business Research, 2015)
The struggle to replace fossil fuel with clean bioenergy has come to an end. The possibility of electric batteries opens a new era for the transportation sector. This revolution is causing a great impact on the automobile sector by replacing fossil fuel with hybrid batteries. As such, there is a huge marketing potential for electric vehicle (EV) charging stations as the popularity of electric vehicles continues to grow. Aside from the potential revenue of owning one, planning and strategic management plays an important part. This research attempts to prove the flexibility of owning and managing an electric vehicle charging station, as with the current pace of the technology revolution it is believed to be a potential major field and a worthy investment.
Keywords: charging; batteries; hybrid; clean; energy